Cochrane Database of Systematic Reviews 2004
DOI: 10.1002/14651858.cd002006.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Position in the second stage of labour for women without epidural anaesthesia

Abstract: Upright or lateral position compared with supine or lithotomy positions. Secondary comparisons with different upright positions and the lateral position were made. Outcomes:Maternal outcomes included pain during delivery, duration of labour, mode of delivery, trauma to the birth canal that required suturing, blood loss greater than 500 ml; fetal outcomes were also described, including admission to intensive care unit and perinatal death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 117 publications
(68 citation statements)
references
References 44 publications
2
62
0
4
Order By: Relevance
“…Cluett 2002;Gupta 2004;Hodnett 2007;Hunter 2007). While position in the first stage of labour may have an independent effect, the position in second stage and other variables (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Cluett 2002;Gupta 2004;Hodnett 2007;Hunter 2007). While position in the first stage of labour may have an independent effect, the position in second stage and other variables (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Women could score more than one birthing position. Birthing positions were defined as: supine (recumbent or semi-recumbent positions), lateral, sitting (4 451 from the horizontal), squatting, standing, use of birthing shell (a plastic plateau giving support to women in squatting position), use of birthing stool, hands and knees, and bath Gupta et al, 2004). Short written information in everyday language explained the positions.…”
Section: Instrumentsmentioning
confidence: 99%
“…Still, studies on this topic are limited and have not explicitly focused on the effect choices in birthing positions have on women's sense of control, especially among women who prefer other than the more common supine positions. Women's choice can play a major role in birthing positions as there is no dominant medical reason for the routine use of a specific position Gupta et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…A Cochrane review concluded that up-right positions were recommended during the second stage, especially for women without epidural anaesthesia (Gupta et al, 2004).…”
Section: Discussionmentioning
confidence: 99%